2022
DOI: 10.1007/s13760-022-02026-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical features, and treatment modalities of facial nerve palsy in COVID-19 patients: a systematic review

Abstract: Background Coronavirus disease 2019 (COVID-19) is responsible for a wide variety of multi-system clinical features. Facial nerve palsy (FNP) is identified as one of the neurological complications of the virus. This work aims to systematically review the clinical picture, laboratory/imaging findings, treatment options, and prognostic factors of FNP in COVID-19 patients. Methods Using six online databases, a search was conducted to include all articles with patients infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Last but not least, some researches have reported that COVID-19 may cause facial nerve palsy (54,55). Mehrdad Estakh et al (11) have shown that there is enough evidence suggesting that patients with COVID-19 infection may present with facial palsy as the initial clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, some researches have reported that COVID-19 may cause facial nerve palsy (54,55). Mehrdad Estakh et al (11) have shown that there is enough evidence suggesting that patients with COVID-19 infection may present with facial palsy as the initial clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of Bell's palsy after SARS-CoV-2 infection has not been investigated. Turki et al [12] reported a complete recovery rate of 62.5% in 32 patients with Bell's palsy after COVID-19 infection, which is similar to the complete recovery rate of 71% [5] for patients with Bell's palsy that were not diagnosed with COVID-19. However, Uysal and Güllüoğlu [13] reported that the complete recovery rate decreased from 88.2% before the COVID-19 pandemic to 28.9% during the COVID-19 pandemic.…”
Section: Jarmentioning
confidence: 60%
“…A systematic review found a pool of 32 patients who had been treated for Bell's palsy, and a combination of antivirals and steroids led to a faster resolution of symptoms than steroids or antivirals alone. 23 Other cranial nerve deficits have occurred in association with COVID-19 infection including oculomotor (CN III) and abducens (CN VI). 15 The vestibulocochlear nerve (CN VIII) was affected in the form of tinnitus or hearing changes in 13.2% of severe COVID-19 survivors, though this may be confounded by commonly used medications such as furosemide in severe infections.…”
Section: Cranial Nerve Palsiesmentioning
confidence: 99%